Development of Open-Ended-Based Mathematics E-Module on Quadrilateral Material of Junior High School - Shalihah, Nurina Fairuz; Wibowo, Teguh; Yuzianah, Dita (Universitas Muhammadiyah Mataram, 2022)
The purpose of this research was to develop an open-ended-based mathematics e-module that is feasible in terms of being valid, practical, and effective. This product used the quadrilateral material of Junior High Schoo l. The method used is the Research and Development (R&D) research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the study, the assessment by material experts and media experts was in the valid category, then the practicality assessment in terms of the results of the questionnaire response analysis of students and teachers met the practical category, and the effective product was seen from the student's test results and analyzed using one-sample t-test the conclusions of the research hypothesis were the average student learning outcomes of the experimental class are greater than minimum completeness 75. With that, the open-ended mathematics e-module product on the quadrilateral material of grade 7 Junior High School can be said to be valid, practical, and effective.